The Relationship Between Mother's Knowledge And Exclusive Breast Feeding To Infants In Medan Labuhan Public Health Center - Sinaga, Taruli Rohana; Sri Dearmaita Purba; Asima Sirait; Agnes Purba; Lasria Kartika (Akupun Tour Publisher, 2023)
Purpose : Exclusive breastfeeding is breast milk given to babies from birth for six months without adding or replacing it with other foods or drinks. Methode : Exclusive breastfeeding should be provided for the first six months of life to achieve optimal growth, development and health. The purpose of this study was to determine the relationship between mother's knowledge and exclusive breastfeeding for infants at the Medan Labuhan Public Health Center. The type of research used is Quantitative Analytical with a cross sectional approach. The population in this study were all mothers who had babies aged 7-24 months who were in the working area of the Medan Labuhan Puskesmas. The sample in this study were 84 respondents, with the sampling technique using Accidental Sampling. Data collection used a questionnaire, and data were analyzed using the chi-square test. Results : The results of this study indicate that the majority of mothers' knowledge about exclusive breastfeeding is lacking and the majority of exclusive breastfeeding to infants is not given in the Medan Labuhan Health Center work area. Disscusion and Conclusion: The conclusion is that there is a relationship between mother's knowledge about exclusive breastfeeding and exclusive breastfeeding for babies in the working area of the Labuhan Health Center.